PENJATUHAN PIDANA TERHADAP TERDAKWA YANG MELAKUKAN TINDAK PIDANA PENGANCAMAN KEPADA PETUGAS SATPAM (STUDI PUTUSAN NOMOR: 215/PID.B/2021/PN.PDG) - Sembiring, Susanti; Tama, Gana Aria (Ensiklopedia of Journal, 2023)
Abstract: Crime always occurs in our environment in various forms. Article 335 Paragraph (1) of the Criminal Code regulates the prohibition of committing the crime of "Forcing With Threats of Violence to Do Something". Where the act is an unlawful act with criminal sanctions for a maximum of 1 (one) year or a maximum fine of Rp. 4,500. But when heartache arises and intends to repay it, sometimes everyone forgets that there is law. Likewise with the criminal act of threatening someone against a Security Unit officer (Satpam), so that there are sanctions and legal processes that must be passed for the perpetrator. The formulation of the problem in this thesis is: First, what are the judge's considerations in imposing a sentence on decision Number 215/Pid.B/2021/PN.Pdg against a defendant who committed the crime of threatening a security guard. Second, how is the criminal application by the judge against the defendant who committed the crime of threatening security guards in decision number 215/Pid.B/2021/PN.Pdg? Research specification is descriptive. The approach method used is a normative juridical approach. The source of the data used is secondary data obtained through document studies and tracing of laws and regulations related to the problems examined in decision Number 215/Pid.B/2021/PN.Pdg. The data obtained were analyzed qualitatively and presented in a qualitative descriptive manner. Based on the results of the research and discussion, it can be concluded as follows: First, the judge's considerations in imposing a sentence on decision Number 215/Pid.B/2021/PN.Pdg against a defendant who committed the crime of threatening security guards based on juridical and non-juridical considerations. Juridical considerations are based on evidence at trial, namely witness statements, expert statements, letters, instructions and statements of the accused. For non-juridical considerations, the judge looks at the defendant's side during the trial. The defendant was polite in court and admitted his actions frankly, the defendant has never been punished, the defendant has reconciled with the victim-witness. Second, the application of the crime against the defendant who committed the crime of threatening a security guard in decision Number 215/Pid.B/2021/PN.Pdg, taking into account the evidence and the defendant's statement, and the fulfillment of the criminal elements in Article 335 Paragraph ( 1) Criminal Code, stated that the defendant Taufik Bakri Called. Taufik Bin Zulbackri was legally and convincingly proven guilty of committing the crime of Coercion With Threats of Violence to Do Something, imposing a sentence on the defendant with imprisonment for 6 (six) months.Keywords: Impeachment, Criminal, Accused, Threats, Security.